Genome-Wide Analysis of Codon Usage and Influencing Factors in Chikungunya Viruses - Butt, Azeem Mehmood (Public Library of Science, 2014)
Chikungunya virus (CHIKV) is an arthropod-borne virus of the family Togaviridae that is transmitted to humans by Aedes spp. mosquitoes. Its genome comprises a 12 kb single-strand positive-sense RNA. In the present study, we report the patterns of synonymous codon usage in 141 CHIKV genomes by calculating several codon usage indices and applying multivariate statistical methods. Relative synonymous codon usage (RSCU) analysis showed that the preferred synonymous codons were G/C and A-ended. A comparative analysis of RSCU between CHIKV and its hosts showed that codon usage patterns of CHIKV are a mixture of coincidence and antagonism. Similarity index analysis showed that the overall codon usage patterns of CHIKV have been strongly influenced by Pan troglodytes and Aedes albopictus during evolution. The overall codon usage bias was low in CHIKV genomes, as inferred from the analysis of effective number of codons (ENC) and codon adaptation index (CAI). Our data suggested that although mutation pressure dominates codon usage in CHIKV, patterns of codon usage in CHIKV are also under the influence of natural selection from its hosts and geography. To the best of our knowledge, this is first report describing codon usage analysis in CHIKV genomes. The findings from this study are expected to increase our understanding of factors involved in viral evolution, and fitness towards hosts and the environment.